The Influence of Entrepreneurial Knowledge, Entrepreneurial Motivation and Self Efficacy on Interest in Entrepreneurship in Accounting Students, Muhammadiyah University of Sidoarjo - Nanda Indriani; Santi Rahma Dewi (Universitas Muhammadiyah Sidoarjo, 2023)
Nanda Indriani. 2022. The Effect of Entrepreneurial Knowledge, Entrepreneurial Motivation and Self Efficacy on Entrepreneurial Interest in Accounting Students of Muhammadiyah University of Sidoarjo. This study aims to determine the effect of entrepreneurial knowledge, entrepreneurial knowledge motivation, and self-efficacy on the entrepreneurial interest of accounting students at the University of Muhammadiyah Sidoarjo. The criteria for the population of this study were all accounting students in 2016 and 2017 who completed entrepreneurship course, namely 451 people. The research sample consisted of 212 people. Making the data obtained by distributing a questionnaire, which the conducted data analysis using multiple linear regression analysis by SPSS version 18.0 program. Results of testing the hypothesis that entrepreneurial knowledge has a positive and significant effect on interest in entrepreneurial knowledge has a positive and significant effect on interest in entrepreneurship, so that the first hypothesis (H1) is accepted. Entrepreneurial motivation has a positive and significant effect on interest in entrepreneurship, so that the second hypothesis (H2) is accepted. Self-efficacy has a positive and significant effect on interest in entrepreneurship, so that the third hypothesis (H3) is accepted.